The Effect of Whey Protein Edible Film Contained Benzoic and Propionic Acid on Total Plate Count, Coliform and Escherichia coli Gouda Cheese - Abdul Manab (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2009)
The purpose of this research was to study effect of using whey protein edible film contained benzoic and propionic acid on coliform and E. coli of gouda cheese during 4 weeks ripening. The result showed that the effect of using benzoic and propionic acid in the application of whey protein edible film at Gouda cheese on the number microorganisms (TPC, Coliform, Escherichia coli) wasn’t significant (P>0,05). During gouda cheese ripening at first month (0 until 4 weeks) there were significant decrease of microorganisms. Benzoic acid was found more effectively decreased the growth of TPC and Escherichia coli, i.e. : 6.5 x 104 cfu/gram to 0.1 x 104 cfu/gram for TPC, and 6.8 x 103 cfu/gram to 0.05x 103 cfu/gram for Escherichia coli. While propionic acid decreased the growth of coliform more effectively, i.e. : 1.9 x 103 cfu/gram to 0.13 x 103 cfu/gram for Coliform. Keywords: Benzoic acid, Propionic acid, whey protein edible film, Gouda cheese